Studentaktiv læring praksisnær undervisning i høyere utdanning - Loeng, Svein (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"Quality in teaching is a recurrent theme in discussions of higher education. We hear about unqualified lecturers and poor instruction, about classes that obfuscate rather than illuminate the subject matter, and teaching that fails to inspire and motivate students for learning. This anthology addresses the challenges university-level pedagogy faces and provides examples of teaching methods that can accommodate these challenges. The objective is to contribute with research-based knowledge, strategies for student-active learning and activities that stimulate learning, underscored with examples from pedagogical practice. The individual articles build on empirical data from four different subject areas: construction contracting, traffic and transport logistics, organizational studies and the compulsory philosophy course for undergraduate students in Norway (Examen philosophicum). This book will be of interest primarily to teachers, advisors and guidance counsellors, and educators responsible for curriculum planning within the higher education sector; however, students will also find it useful. The authors are researchers and instructors all working in various ways with learning processes at Nord University."